The Use of Performance Measures in Incentive Contracting - Baker, George (American Economic Review, 2000)
The strength of incentives used in an organization and the productivity of employees that results from these incentives depend to a large degree on the characteristics of the performance measures available to the organization. Some employees work under high-powered explicit incentive contracts, while others have no explicit incentive contracts at all. The ability of agency theory to predict the pattern of incentive provision in organizations has not been very impressive, and the divergence between the prescriptions of agency theory and the actual practice of firms has been widely noted. This paper (along with both other papers in this session [Edward P. Lazear, 2000; Canice Prendergast, 2000]) attempts to fill some of the gap between theory and practice. I examine the characteristics of performance measures (those data on which explicit incentive contracts are based) to understand how firms use incentive contracting, and to predict the use of incentives in practice.